Unveiling the pathogenic mechanisms of NPR2 missense variants: insights into the genotype-associated severity in acromesomelic dysplasia and short stature - Badawi, Sally; Varghese, Divya Saro; Raj, Anjana; John, Anne; Al-Musafir, Hamda S.; Al-Ghamari, Ahmed J.; Alshamsi, Alreem R.; Ouda, Sara H.; Al-Dirbashi, Ghayth; Ali, Bassam R. (Frontiers in Cell and Developmental Biology, 2023)
Natriuretic peptide receptor 2 (NPR2 or NPR-B) plays a central role in growth development and bone morphogenesis and therefore loss-of-function variations in NPR2 gene have been reported to cause Acromesomelic Dysplasia, Maroteaux type 1 and short stature. While several hypotheses have been proposed to underlie the pathogenic mechanisms responsible for these conditions, the exact mechanisms, and functional characteristics of many of those variants and their correlations with the clinical manifestations have not been fully established. In this study, we examined eight NPR2 genetic missense variants (p.Leu51Pro, p.Gly123Val, p.Leu314Arg, p.Arg318Gly, p.Arg388Gln, p.Arg495Cys, p.Arg557His and p.Arg932Cys) Acromesomelic Dysplasia, Maroteaux type 1 and short stature located on diverse domains and broadly classified as variants of uncertain significance. The evaluated variants are either reported in patients with acromesomelic dysplasia in the homozygous state or short stature in the heterozygous state. Our investigation included the evaluation of their expression, subcellular trafficking and localization, N-glycosylation profiles, and cyclic guanosine monophosphate (cGMP) production activity. Our results indicate that variants p.Leu51Pro, p.Gly123Val, p.Leu314Arg, p.Arg388Gln have defective cellular trafficking, being sequestered within the endoplasmic reticulum (ER), and consequently impaired cGMP production ability. Conversely, variants p.Arg318Gly, p.Arg495Cys, and p.Arg557His seem to display a non-statistically significant behavior that is slightly comparable to WT-NPR2. On the other hand, p.Arg932Cys which is located within the guanylyl cyclase active site displayed normal cellular trafficking profile albeit with defective cGMP production suggesting enzymatic loss of activity as its underlying mechanism. Collectively, our data highlights the genotype-phenotype relationship that might be responsible for the milder symptoms observed in short stature compared to acromesomelic dysplasia. This study enhances our understanding of the functional consequences of several NPR2 variants, shedding light on their mechanisms and roles in related genetic disorders which might also help in their pathogenicity re-classification.Deleted: have displayed a significant decrease in the production of 296 cGMP.